Prevalences of pathogenic and non-pathogenic Vibrio parahaemolyticus in mollusks from the Spanish Mediterranean Coast - Lopez-Joven, Carmen; de Blas, Ignacio; Furones, M. Dolores; Roque, Ana (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus is a well-recognized pathogen of humans. To better understand the ecology of the human-pathogenic variants of this bacterium in the environment, a study on the prevalence in bivalves of pathogenic variants (tlh + and tdh+ and/or trh+) versus a nonpathogenic one (only tlh+ as species marker for V. parahaemolyticus), was performed in two bays in Catalonia, Spain. Environmental factors that might affect dynamics of both variants of V. parahaemolyticus were taken into account. The results showed that the global prevalence of total V. parahaemolyticus found in both bays was 14.2% (207/1459). It was, however, significantly dependent on sampling point, campaign (year) and bivalve species. Pathogenic variants of V. parahaemolyticus (tdh+ and/or trh+) were detected in 3.8% of the samples (56/1459), meaning that the proportion of bivalves who contained tlh gene were contaminated by pathogenic V. parahaemolyticus strains is 27.1% (56/207). Moreover, the presence of pathogenic V. parahaemolyticus (trh+) was significantly correlated with water salinity, thus the probability of finding pathogenic V. parahaemolyticus decreased 1.45 times with every salinity unit (ppt) increased. Additionally, data showed that V. parahaemolyticus could establish close associations with Ruditapes spp. (P-value < 0.001), which could enhance the transmission of illness to human by pathogenic variants, when clams were eaten raw or slightly cooked. This study provides information on the abundance, ecology and characteristics of total and human-pathogenic V. parahaemolyticus variants associated with bivalves cultured in the Spanish Mediterranean Coast.